Clanless Children and Inheritance in the Indigenous Batak Community: A Case Study of Supreme Court Decision No. 1537 K/Pdt/2012 - Naiborhu, Yoshua Putra Dinata; Saraswati, Rika; Nurhayati, B. Resti; Boputra, Emanuel (APPTHI, 2025)
The Batak people adhere to a patrilineal family system where the family system is drawn from the paternal line. The status of a child without a surname has consequences for inheritance, so that the inheritance process for descendants who do not have a surname causes problems in the future. The purpose of this study is to determine children without a surname according to the provisions of the Batak traditional community and the legal consequences for children without a surname as heirs. The approach method in this paper is normative-empirical research. The results of the study indicate that children can be born without a surname due to parental marriages that violate Batak customs, or lose their surname due to removal by traditional elders due to actions that embarrass, threaten, or provoke the community. Furthermore, Supreme Court Decision Number 1537 K / Pdt / 2012 in its decision, even if the child does not have a surname, as long as it can be proven that the child is the biological child of the deceased parent (heir) then the child has the right to appear as an heir.